Evolutionary-Fragmentary Model of the Routing Problem - Kozin, I. V.; Kryvtsun, O. V.; Pinchuk, V. P. (Cybernetics and systems analysis, 2015)
One of the variants of the routing problem on a plane integer lattice is considered. It is shown that this problem can be represented as a problem of searching for words with certain properties over a finite alphabet. In turn, the problem of finding optimal words can be considered as a problem of fragmentary structure. A combinatorial estimate for the set of feasible words is derived and the lower bound of the density is established for the problem of finding optimal line density. An evolutionary-fragmentary model of the routing problem is constructed. Optimal and near-optimal solutions are obtained for this problem for small dimensions.